1989
DOI: 10.1073/pnas.86.13.5074
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a functional idiotypic network among natural antibodies in normal mice.

Abstract: We monitored in normal adult BALB/c mice the serum concentrations of four natural IgM antibodies, two of which show idiotypic complementarity in in vitro assays. In each individual, serum concentrations ofall four idiotypes were found to fluctuate in complex dynamical patterns with low correlation. The spectral power of some such patterns was found to be compatible with the existence of a chaotic regime. Groups of normal adult mice were injected intravenously with low' (10 ng) or moderate (10 ,ug) doses of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 23 publications
8
55
0
3
Order By: Relevance
“…9. A more simplified description would require only the presence of B-memory cells for providing signalling to T H , skipping any discussion on memory generation in the B-cell network [4,27]. 10.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…9. A more simplified description would require only the presence of B-memory cells for providing signalling to T H , skipping any discussion on memory generation in the B-cell network [4,27]. 10.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Studies with germ-free mice, however, have shown activated spleen lymphocyte numbers and serum IgM levels very similar to those of specific pathogen-free and normal animals (1,2). Coutinho, Varela and co-workers (3,4) have shown that natural antibodies present complex dynamic activity in the absence of external antigenic stimulation, as well as a high degree of con- nectivity with each other and with other self components (5)(6)(7). Idiotypic connectivity and self-recognition, in agreement with the ideas of Jerne (8), lead to the formation of a network, where the elements are in equilibrium and therefore are not activated to react with self.…”
Section: Introductionmentioning
confidence: 61%
“…These time series with a sequence of daily concentration values measured in humans are more relevant for an interpretation than the early data from mice with a seven day interval 32 . The set of data (< 70-80 uninterrupted serial time points) was too small for a reliable determination of the fractal dimension of the time series 33,34 .…”
Section: Normal Antibody Dynamics In Bloodmentioning
confidence: 99%
“…The shorter lifetime of the B cells with a daily renewal of about 20-25% 12 required the understanding of the anti-idiotype network 32,38 and the polyclonal activation of memory B cells 39 to explain the maintenance of the serological memory.…”
Section: Natural Dynamics Of the Immune Systemmentioning
confidence: 99%